2012
DOI: 10.1097/rlu.0b013e3182639747
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Lesion Glycolysis and Tumor Lesion Proliferation for Response Prediction and Prognostic Differentiation in Patients With Advanced Non–Small Cell Lung Cancer Treated With Erlotinib

Abstract: In patients with advanced NSCLC, percentage changes of TLG and TLP and absolute residual TLG and TLP levels under erlotinib treatment emerged as strong predictive factors for PFS. Our findings indicate that a cutoff value of 20% or 30% for definition of metabolic response measured by percentage changes of TLG and TLP provides suitable results for response prediction, which should be further validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…Although patients carrying mutations of the EGFR gene generally respond better to tyrosine kinase inhibitors (TKIs) [1], erlotinib may improve survival even in subjects with EGFR wild-type tumors [2]. Several studies have shown that FDG-PET is a useful imaging modality for predicting response to erlotinib in patients with non-small cell lung cancer (NSCLC) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However, most of these studies used only the primary tumor as the target lesion for sequential imaging [3][4][5][6][7][8][9][10][11][12], and treatment response was largely assessed using the European Organization for Research and Treatment of Cancer (EORTC) criteria [3][4][5][6][7][8][9]20].…”
Section: Introductionmentioning
confidence: 99%
“…Although patients carrying mutations of the EGFR gene generally respond better to tyrosine kinase inhibitors (TKIs) [1], erlotinib may improve survival even in subjects with EGFR wild-type tumors [2]. Several studies have shown that FDG-PET is a useful imaging modality for predicting response to erlotinib in patients with non-small cell lung cancer (NSCLC) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However, most of these studies used only the primary tumor as the target lesion for sequential imaging [3][4][5][6][7][8][9][10][11][12], and treatment response was largely assessed using the European Organization for Research and Treatment of Cancer (EORTC) criteria [3][4][5][6][7][8][9]20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the correlation with proliferation is partially shown in response to treatment. The association with progression-free survival and 18 F-FLT uptake was shown in patients treated with erlotinib (73). In 30 patients with stage IV non-small cell lung cancer imaged before, 1 wk, and 6 wk after the start of erlotinib treatment, 18 F-FLT and 18 F-FDG PET imaging was done.…”
Section: Lung Cancermentioning
confidence: 99%
“…For non-small cell lung cancer (NSCLC), 18 F-FDG PET/CT image quantification has been shown to provide prognostic information. PET image-derived features, including metabolically active tumor volume (MATV), mean standardized uptake value (SUV mean ), and total lesion glycolysis (TLG, defined as MATV · SUV mean ), have been shown to provide an accurate assessment of tumor burden with potentially higher prognostic value than standard maximum SUV (SUV max ), for both surgical and nonsurgical patients (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%